Effects of lactic acid bacteria exposed to extreme conditions on yoghurt quality - Gökhan Akarca; Ayşe Janseli Denizkara (Mljekarstvo)
In this study, two bacterial strains used in the production of yoghurt were subjected to three distinct stress conditions (low pressure, infrared light, and low pressure + infrared light) and then used as starter cultures for yoghurt production. The obtained results revealed that the bacterial stress response mechanisms, especially those of bacteria exposed to low pressure, positively affected the physicochemical, textural, and microbiological quality during storage of yoghurts produced with these bacteria. In addition, it was found that prolonging the exposure time to stress conditions increased this effect even more. The samples subjected to low pressure for 2 hours had the shortest fermentation time among all samples, while the samples subjected to infrared light for 2 hours had the longest fermentation time. Yoghurts produced with bacteria subjected to low pressure conditions had more organic acids and aroma components and less syneresis during storage compared to other samples. Furthermore, it was determined that yoghurt samples produced with bacteria exposed to stress conditions had higher L* and a* values, lower b* values, improved textural values, and higher bacterial counts during the 7-day storage period compared to control samples.